2013
DOI: 10.1007/s12272-013-0290-4
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet, anticoagulant, and profibrinolytic activities of cudratricusxanthone A

Abstract: Cudratricusxanthone A (CTXA), a natural bioactive compound extracted from the roots of Cudrania tricuspidata Bureau, is known to possess hepatoprotective, antiproliferative and anti-inflammatory activities. However, antiplatelet, anticoagulant, and profibrinolytic properties have not been studied. The anticoagulant activities of CTXA were measured by monitoring activated partial thromboplastin-time (aPTT), prothrombin time (PT), and the activities of cell-based thrombin and activated factor X (FXa). The effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 27 publications
0
26
0
1
Order By: Relevance
“…Compounds isolated from C. tricuspidata roots can be divided into chromones (1-2), isoflavonoids (3)(4)(5)(6), flavonols (7)(8), flavanonols (9-10) and flavanones (11)(12)(13)(14)(15)(16)(17). Overall, flavanones showed stronger pancreatic lipase inhibition than other groups in our assay system (Table 1).…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Compounds isolated from C. tricuspidata roots can be divided into chromones (1-2), isoflavonoids (3)(4)(5)(6), flavonols (7)(8), flavanonols (9-10) and flavanones (11)(12)(13)(14)(15)(16)(17). Overall, flavanones showed stronger pancreatic lipase inhibition than other groups in our assay system (Table 1).…”
mentioning
confidence: 87%
“…1 Previous studies reported the isolation of diverse and xanthones their antitumor and anti-inflammatory activity. [2][3][4][5][6] Obesity is a global health problem and associated with several disorders, including diabetes, hypertension, atherosclerosis and cancer. In modern days, increased fat intake is an important factor of obesity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Primary human umbilical vein endothelial cells (HUVECs) were obtained from Cambrex Bio Science (Charles City, IA) and maintained as described previously [7,[15][16][17][18][19][20][21]. Briefly, the cells were cultured to confluency at 37°C and 5 % CO 2 in EBM-2 basal media supplemented with growth supplements (Cambrex Bio Science).…”
Section: Cell Culturementioning
confidence: 99%
“…Primary HUVECs were obtained from Cambrex Bio Science (Charles City, IA) and maintained as described in previous studies [25,[28][29][30][31][32][33][34][35]. Briefly, the cells were cultured to confluency at 37°C and 5 % CO 2 in EBM-2 (endothelial basal medium) supplemented with growth supplements (Cambrex Bio Science).…”
Section: Cell Culturementioning
confidence: 99%